MORAL PROBLEMS DEPICTED IN KRISHNA SOBTI’S NOVELS - Uma Devi, Khuraijam (ShodhKosh: Journal of Visual and Performing Arts, 2022)
On the Indian literature scene, it is known that the moral problems depicted in the novels of the famous Hindi story writer Krishna Sobtiji. Krishnaji has reviewed all those traditions and loyalties in her novels. In her novels, the writer has mostly presented the depiction of middle class families and their moral conditions. For example, respecting elders, maintaining dignity, serving others, trying to protect one’s chastity with all her might, etc. The main problem of this novel is that of Pasho. It is the story of ’Pasho’, who is bound by traditions and customs, slipping and going astray. Once ’Pasho’ got separated from the branch, she had to pass through many thorny paths and trails. ‘Daar se bichhudi’ means a woman who is free from the clutches of social taboos and family rules and regulations. But who listens to the cry of a helpless woman in a male-dominated society. In this novel, Sheikhji has been depicted as a human moral value. In the novel ‘Mitro Marjani’, the writer has presented a woman who, despite being the wife of ‘Mitro’, Sardar Lal, is troubled by sexual power and shamelessness and is immersed in luxury, love, and is busy teasing and taunting others. Although, the writer has shown her as an open-hearted woman. ‘Mitro’, on one hand, is a fierce rebel and on the other hand has a deep faith in wisdom and human values. ‘Mitro’, who courageously rejects the allure of ideals and the fear of society, has been presented as a woman who challenges morality when she is not sexually satisfied by her husband. In the novel ’Yaaron Ke Yaar’, Krishnaji has presented bureaucracy, corruption, degradation through the reality of urban and office life and at the same time a working woman typist like Miss Tamasha who becomes a call girl to earn more money. In the novel ’Tin Pahad’, the writer has presented the life of such a woman through Jaya who is rejected even after being engaged, and is deprived of the rights she gets as a daughter and daughter-in-law. This Tin Pahad is a symbol of three shocks. First, Shri rejecting his fiancé after marrying ’Edna’; second, marrying Jaya Shri first as a daughter and later as a daughter-in-law; and third, the desire to get connected to Tapan has been depicted in this novel. In the novel ’Sunflowers of Darkness’, the writer has also thrown light on the problems of moral values. In this, the mental state of ’Ratti’ who was raped in childhood has been presented. In this novel, through Ratti who was raped in childhood, a woman has been portrayed who cannot forget the bitter memories even if she wants to, who loves solitude, is strong and fearless and who has gone through the failures of life and is the story of growing, desiring and achieving the sunflower of future hopes. In this novel, all moral values ​​are proved false for Ratti. The writer has portrayed moral values ​​and traditions in her novels.